Regeneration of the nerves in the aerial cavity with an artificial nerve conduit --reconstruction of chorda tympani nerve gaps-. - Toshiaki Yamanaka; Hiroshi Hosoi; Takayuki Murai; Takehiko Kobayashi; Yuji Inada; Tatsuo Nakamura (PLoS ONE, 2014)
Objectives/hypothesis Due to its anatomical features, the chorda tympani nerve (CTN) is sometimes sacrificed during middle ear surgery, resulting in taste dysfunction. We examined the effect of placing an artificial nerve conduit, a polyglycolic acid (PGA)-collagen tube, across the gap in the section of the resected chorda tympani nerve (CTN) running through the tympanic cavity. Methods The CTN was reconstructed with a PGA-collagen tube in three patients with taste disturbance who underwent CTN resection. To evaluate the effect of the reconstruction procedure on the patients' gustatory function, we measured the patients' electrogustometry (EGM) thresholds. The patients were followed-up for at least two years. Results Gustatory function was completely restored in all of the patients after the reconstruction. The patients' EGM thresholds exhibited early improvements within one to two weeks and had returned to their normal ranges within three months. They subsequently remained stable throughout the two-year follow-up period. In a patient who underwent a second surgical procedure, it was found that the PGA-collagen tube used in the first surgical procedure had been absorbed and replaced by new CTN fibers with blood vessels on their surfaces. Conclusion These results suggest that reconstruction of the CTN with an artificial nerve conduit, a PGA-collagen tube, allows functional and morphological regeneration of the nerve and facilitates the recovery of taste function. PGA-collagen tubes might be useful for repairing CTNs that are resected during middle ear surgery. Further research is required to confirm these preliminary results although this is the first report to describe the successful regeneration of a nerve running through an aerial space.